2001
DOI: 10.1073/pnas.141042198
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin-deficient mice show altered responses to antipsychotic drugs

Abstract: The peptide transmitter neurotensin (NT) exerts diverse neurochemical effects that resemble those seen after acute administration of antipsychotic drugs (APDs). These drugs also induce NT expression in the striatum; this and other convergent findings have led to the suggestion that NT may mediate some APD effects. Here, we demonstrate that the ability of the typical APD haloperidol to induce Fos expression in the dorsolateral striatum is markedly attenuated in NT-null mutant mice. The induction of Fos and NT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 59 publications
2
29
0
Order By: Relevance
“…Our results confirm and extend the previous findings of Fadel et al (2001) and Dobner et al (2001) concerning the involvement of NT neurotransmission in APD-induced Fos expression in the CPu. We did not, however, observe any common effects of the NT receptor antagonist on APDinduced Fos-expression in limbic brain regions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results confirm and extend the previous findings of Fadel et al (2001) and Dobner et al (2001) concerning the involvement of NT neurotransmission in APD-induced Fos expression in the CPu. We did not, however, observe any common effects of the NT receptor antagonist on APDinduced Fos-expression in limbic brain regions.…”
Section: Discussionsupporting
confidence: 92%
“…Two recent studies have confirmed that NT neurotransmission partly mediates haloperidol-induced Fos expression in the CPu, but not in the NAcc Dobner et al, 2001). This was shown using the NT receptor antagonist SR 48692 and transgenic mice lacking a functional NT/NN gene, respectively.…”
Section: Introductionmentioning
confidence: 96%
“…Catalepsy was evaluated using the inclined plan procedure (Dobner et al, 2001). Mice were placed in a mesh wire grid inclined to an angle of 701.…”
Section: Catalepsymentioning
confidence: 99%
“…The two main families of transcripts studied so far include Fos and striatal neuropeptides such as enkephalin and neurotensin (Herdegen and Leah, 1998;Steiner and Gerfen, 1998). The effect of neuroleptics on opioid neuropeptide expression is seen as an adaptative phenomenon to re-establish the normal activity of dopamine systems (Steiner and Gerfen, 1998), whereas it has been suggested that neurotensin is required for the activation of specific populations of striatal neurons by typical antipsychotics (Dobner et al, 2001). Our results demonstrate that the genetic deletion of NGFI-B also interferes with the effect of haloperidol on striatal enkephalin and neurotensin expression.…”
Section: Ngfi-b(+/+) Ngfi-b(-/-) Ngfi-b(+/+) Ngfi-b(-/mentioning
confidence: 99%
“…To examine the potential role of NT in fat deposition and obesity, we initially compared NT-deficient mice 10,11 to wild type littermates fed a standard diet (18% kcal from fat) for 6 months. Average body length, small bowel weight and length, villus height and crypt number did not differ between genotypes (Extended Data Fig.…”
mentioning
confidence: 99%